The Effect of Full Use of e-Booklet Media on Mother's Knowledge and Its Relationship with the Level of Nutrition Consumption of Elementary School Children Who Experience Excess Nutrition - Maulida Febri Rahmata; Batianus Doddy Riyadi; Juin Hadisuyitno; Suprajitno Suprajitno (Journal of Ners and Midwifery, 2023)
The prevalence of overweight and obesity among children has become a global epidemic. The causes of obesity are multifactorial. Changes in lifestyle that lead to westernization and sedentary result in changes in eating patterns in children. The objective of this study was to determine the differences in maternal nutritional knowledge before and after counseling on balanced nutrition using e-booklets and their correlation to the consumption level of elementary school children who experience excess nutrition. The research design used was a pre-experimental one-group pretest-posttest design. A sample of 31 mothers and children who are experiencing excess nutrition from SDN 1 and 2 Sambirejo, Trenggalek regency was selected by purposive sampling. Data analysis employed the Paired Sample T-Test and Chi-Square test. There was an increase in the average score of mothers' knowledge from 69.03 to 77.41 with a p-value = 0.003 with ï¡ = 0.05. However, there was no correlation between a mother's knowledge and intake of energy, carbohydrates, protein, and fat. Nutrition counseling using e-booklet media can increase mothers' knowledge but it is not related to the intake of elementary school children who have more nutrition